Analysis of the Efficiency of the Use of Potato Farming Production Inputs in Ngaduman, Getasan District, Semarang Regency - Yohana Aprilia; Tinjung Mary Prihtanti (Syntax Idea)
The right allocation of production inputs will provide benefits for farmers. Farmers cultivate potato with different allocation of production inputs. The wrong understanding of the assumption that the more production inputs allocated, the higher the productivity of the crops cultivated, is the cause of the higher production costs incurred by farmers, causing inefficiency. The purpose of this study was to analyze the effect of the use of production inputs and the allocative efficiency of seeds, fertilizers Phonska, fertilizers Za, pesticides, and labor on the productivity level of potatos farming. The research was conducted through interviews with 30 potato farmers as respondents who were selected through purposive sampling technique. The data were analyzed using the Cobb-Douglas production function model and allocative efficiency analysis. The results showed that land area and labor had a significant positive effect on potatos productivity, while seeds, fertilizers, and pesticides had no significant effect on potatos productivity. In potato farming in Ngaduman, seeds and labor production inputs are not allocatively efficient, while production inputs for fertilizers Phonska , fertiluzers Za and pesticide are allocatively inefficient.